MEMBANGUN KESADARAN SOSIAL ANAK USIA DINI (AUD) MELALUI MODEL PEMBELAJARAN MATEMATIKA KREATIF - Jamiah, Yulis (Jurnal Pendidikan Matematika dan IPA, 2010)
Early age is generally the period of playing for children. The interaction among them when they are playing together actually shows social values. The values such as helping each other, togetherness are built up within them when they are playing. This social system consists of children activities where their interaction, contact, and togetherness are based on certain patterns. The children are directed toward psychological situation and condition to develop happiness, enjoying beauty, expressing feeling through words and rhythm which make learning more enjoyable. Keyword: social awareness, creative mathematic